Risk Factors of Neonatal Death in Meconium Aspiration Syndrome at Trang Hospital - Treeratanapaiboon, Nopawan (Journal of The Department of Medical Services, 2022)
Background: Meconium aspiration syndrome ( MAS ) is an important cause of acute respiratory distress in newborn , which has serious complication and high mortality rate. Objectives: To determine the incidence , outcome and complications of infants with MAS and prognostic factors of this conditions at Trang Hospital. Methods: This study was a retrospective descriptive study. Medical records of infants who diagnosed with MAS at Trang hospital between 1st October 2016 and 30nd September 2019 were reviewed. Data on maternal and neonatal demographics , clinical course and outcome were recorded. Results: Meconium stained amniotic fluid (MSAF) was found in 556 neonates. Two hundred three neonates of MAS cases were enrolled , (36.5% of MSAF) , one hundred and fifty-nine newborn was born at Trang Hospital The incidence of MAS was 14.76 per 1000 live birth. Fifteen cases of MAS died ( mortality 7.4%) and 38.9% of MAS needed mechanical ventilation. The most common cause of death was persistent pulmonary hypertension of newborn (PPHN, 100 % ). Other cause was sepsis ( 87.6%). The significant poor prognostic factor of MAS were non vigorous neonate , APGAR score at 1 min and at 5 min < 3 , on mechanical ventilation , MAS with complication : PPHN , sepsis , birth asphyxia , pneumothorax and pulmonary hemorrhage. Conclusions: Incidence of MAS during this period at Trang Hospital was 14.76 per 1000 live birth. The mortality rate was 7.4%. Poor prognostic factor was non vigorous neonate, severe birth asphyxia , on mechanical ventilation , PPHN , sepsis , pneumothorax and pulmonary hemorrhage The most common cause of death was PPHN.